(untitled) (Journal of Nematode Morphology and Systematics, 2012)
The status of 15 species belonging to the genus Tylencholaimus, which have been described along the last 12 years, is analysed and discussed. Nine species are confi rmed as valid, including Amphitylencholaimus cosmos, which is transferred to Tylencholaimus; fi ve species are regarded as junior synonyms of other previously known, namely T. japonicus of T. ibericus, Opisthotylencholaimus karnataki of T. intermedius, T. lokus of T. imperanus, Protylencholaimus longisaccus of T. vulvulatus, and T. vanguimus of T. micronanus; and T. annulatus is transferred to the genus Cricodorylaimus. The intrageneric taxonomy of Tylencholaimus is briefl y commented. Finally, an updated list of its species as well as a key to their identifi cation are provided.